Redefining Poverty and Its Measurement: An Islamic Political Economy Perspectives - Fawad Khaleel (Global Review of Islamic Economics and Business, 2016)
Islamic economists have always taken the position on the intrinsic capability of poverty alleviation in the Islamic economic model. The poverty, in economics and social sciences, is taken in the context of economic deprivation. Among the multitudinous meanings of poverty, generally it is defined as the lack of income, human underdevelopment, social exclusion, ill being, unsustainable livelihood, lack of basic needs, vulnerability and relative deprivation, while multifarious methodologies like head count ratio, poverty gap ratio, income gap ratio and Sen index are used to measure the poverty. The poverty in the developed countries mostly is identified relative to the average level of income as compared to developing countries which usually define it on the grounds of absolute standard of living. Islamic model clearly addresses poverty in number of ways and even considers it as a threat to faith and recommends alleviating it through different tools like zakat, which is the negative rate of return on savings. The tools prescribed in Islam for counteracting poverty are designed on different conceptual grounds to conventional poverty reduction tools, similarly Islam’s conceptually constructed understanding on: lack of income, human underdevelopment, social exclusion, ill being, unsustainable livelihood, lack of basic needs, vulnerability and relative deprivation differs in its context and in its intrinsic intellectual positioning to the conventional interpretation of these concepts. Inductively therefore, Islam’s idea of, ‘what is poverty?’ and ‘How it can be measured’, is distinct and different to the general perception of poverty. This paper objectively examines the subjective meaning of poverty within Islam, through analysing the intellectual rigour on poverty in the transcendental sources of Islam along with the conceptual construction of Al Ghazali’s work on happiness. It further applies the uniform principles of maqasid al shariah (objectives of Islamic law) and nisab (standard for Zakat to be liable) in an attempt to develop the understanding of monetary measures, which can be used to identify ‘poor and needy’ within an economy. The results should provide the basic argument for the distinction on Islamic concept of poverty and a framework in which such definition can translate into the categorisation of ‘poor’ within an economy; along with some foundational understanding of Islamic value approach on monetary measurement of poverty.